Variation and Change of Upwelling Dynamics Detected in the World’s Eastern Boundary Upwelling Systems - Abrahams, Amieroh; Schlegel, Robert W.; Smit, Albertus J. (Frontiers in Marine Science, 2021)
Global increases in temperature are altering land-sea temperature gradients. Bakun (1990) hypothesised that changes within these gradients will directly affect atmospheric pressure cells associated with the development of winds, and will consequently impact upwelling patterns within ecologically important Eastern Boundary Upwelling Systems (EBUS). In this study we used NOAA Optimally Interpolated sea surface temperature (SST) and ERA 5 reanalysis wind products to calculate a series of metrics related to upwelling, and used these to objectively describe upwelling signals throughout the four EBUS during summer months over the last 37 years (1982-2019). We found that SST increased, and the number of upwelling signals decreased at three of the four EBUS, but the results yielded weak evidence to suggest increases in the intensity of upwelling across all EBUS. The Humboldt Current system showed opposite trends to the other EBUS, with a decrease in SST and increase in the number of upwelling signals detected. Overall, these findings do not support the Bakun (1990) hypothesis.